Pengaruh Kompensasi Terhadap Motivasi Dan Dampaknya Terhadap Kinerja Dosen Di Sekolah Tinggi Agama Islam Negeri Jember: The Influence of Compensation on Motivation and Its Impact on Lecturer Performance at the State Islamic College of Jember - Babun Suharto (Fenomena, 2002)
In the context of Indonesian higher education transformation, lecturer performance remains a critical yet often underutilized factor in achieving institutional excellence. Grounded in motivation and compensation theory, this study investigates the direct and indirect effects of financial and non-financial compensation on intrinsic motivation and lecturer performance. The research employed an explanatory quantitative method with path analysis, using all permanent lecturers at STAIN Jember as the census sample. Data were collected through questionnaires, interviews, and documentation. The findings reveal that non-financial compensation significantly influences intrinsic motivation (beta = 0.618), whereas financial compensation shows no significant effect on either intrinsic motivation (beta = -0.143) or lecturer performance (beta = -0.058). Moreover, intrinsic motivation itself does not significantly mediate the relationship between compensation and performance. The study concludes that non-financial factors such as promotion fairness, training opportunities, work facilities, and a supportive atmosphere are more pivotal in fostering lecturer motivation. It is recommended that STAIN Jember prioritize improving non-financial compensation to enhance intrinsic motivation, though further research is needed to identify other determinants of lecturer performance. Dalam konteks transformasi pendidikan tinggi di Indonesia, kinerja dosen masih menjadi elemen kritis yang kerap belum optimal dalam mendukung keunggulan institusi. Berlandaskan teori motivasi dan kompensasi, penelitian ini menguji pengaruh langsung dan tidak langsung kompensasi finansial dan nonfinansial terhadap motivasi intrinsik serta kinerja dosen. Metode penelitian menggunakan pendekatan kuantitatif eksplanatori dengan analisis jalur, melibatkan seluruh dosen tetap STAIN Jember sebagai sensus. Data dikumpulkan melalui kuesioner, wawancara, dan dokumentasi. Temuan menunjukkan bahwa kompensasi nonfinansial berpengaruh signifikan terhadap motivasi intrinsik (beta 0,618), sementara kompensasi finansial tidak berpengaruh signifikan terhadap motivasi intrinsik (beta -0,143) maupun kinerja dosen (beta -0,058). Motivasi intrinsik juga tidak memediasi hubungan antara kompensasi dan kinerja secara signifikan. Kesimpulannya, faktor nonfinansial seperti keadilan promosi, pelatihan, fasilitas kerja, dan suasana kerja yang kondusif lebih berperan dalam meningkatkan motivasi dosen. Disarankan agar STAIN Jember memprioritaskan peningkatan kompensasi nonfinansial untuk memperkuat motivasi intrinsik, meskipun penelitian lanjutan diperlukan untuk mengidentifikasi determinan lain kinerja dosen.